Positive Psychotherapy Improves Cardiac Electrical Stability and Mood in ICD Patients: PAM-ICD Trial Results. Issue 3 (29th April 2021) - Serber, Eva R.; Christon, Lillian M.; Fava, Joseph L.; Verrier, Richard L.; Nearing, Bruce D.; Buxton, Alfred E.; Gold, Michael R.; Rodrigue, James R.; Frisch, Michael B.
Abstract : Supplemental digital content is available in the text.